Search for New Phenomena in $t\bar{t}$ Events With Large Missing Transverse Momentum in Proton-Proton Collisions at $\sqrt{s}=7$ TeV with the ATLAS Detector - ATLAS collaboration (3017 authors) (2011)
A search for new phenomena in ttbar events with large missing transverse momentum in proton-proton collisions at a center-of-mass energy of 7 TeV is presented. The measurement is based on 1.04 fb^-1 of data collected with the ATLAS detector at the LHC. The search is carried out in the single-lepton channel, characterized by an isolated lepton of high transverse momentum, four or more jets and large missing transverse momentum. Contributions to this final state may arise from a number of Standard Model extensions. The results are interpreted in terms of a model where new top-quark partners are pair-produced and each decay to an on-shell top (or antitop) quark and a long-lived undetected neutral particle. The data are found to be consistent with Standard Model expectations. A limit at 95% confidence level is set excluding a cross-section times branching ratio of 1.1 pb for a top-partner mass of 420 GeV and a neutral particle mass less than 10 GeV. In a model of exotic fourth generation quarks, top-partner masses are excluded up to 420 GeV and neutral particle masses up to 140 GeV.